Disease assessment concepts and the advancements made in improving the accuracy and precision of plant disease data - Nutter, Forrest W.; Esker, Paul David; Coelho-Netto, Rosalee Albuquerque (Plant disease epidemiology: facing challenges of the 21st Century: Under the aegis of an International Plant Disease Epidemiology Workshop held at Landernau, France, 10-15th April, 2005, 2006)
New concepts in phytopathometry continue to emerge, such as the evolution of the concept of pathogen intensity versus the well-established concept of disease intensity. The concept of pathogen severity, defined as the quantitative measurement of the amount of pathogen per sampling unit has also emerged in response to the now commonplace development of quantitative molecular detection tools. Although the concept of disease severity, i.e., the amount of disease per sampling unit, is a well-established concept, the accuracy and precision of visual estimates of disease severity is often questioned. This article will review disease assessment concepts, as well as the methods and assessment aides currently available to improve the accuracy and precision of visually-based disease severity data. The accuracy and precision of visual disease severity assessments can be improved by quantitatively measuring and comparing the accuracy and precision of rates and/or assessment methods using linear regression, by using computer-based disease assessment training programmes, and by developing and using diagrammatic keys (standard area diagrams). © 2006 Springer.